The Generalized Artin Primitive Root Conjecture (European Journal of Pure and Applied Mathematics, 2018)
Asymptotic formulas for the number of integers with the primitive root 2, and the generalized Artin conjecture for subsets of composite integers with fixed admissible primitive roots \(u eq ± 1,v^2\), are presented here.
Keywords: Primitive root; Generalized primitive root.